2009
DOI: 10.1638/2008-0087.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Infrared Thermography to Detect Thermographic Changes in Mule Deer (Odocoileus hemionus) Experimentally Infected with Foot-and-Mouth Disease

Abstract: Infrared thermography (IRT) measures the heat emitted from a surface, displays that information as a pictorial representation called a thermogram, and is capable of being a remote, noninvasive technology that provides information on the health of an animal. Foot-and-mouth disease (FMD) caused by FMD virus (FMDV) is a severe, highly communicable viral disease of cloven-hoofed animals, including both domestic and wild ruminants. Early detection of the disease may reduce economic loss and loss of susceptible wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 9 publications
5
44
1
1
Order By: Relevance
“…Positive research outcomes prompted scientists to investigate the effectiveness of thermographic methods in diagnosing non-invasive diseases in wild animals. Dunbar et al (2009) used infrared thermography to detect temperature changes in mule deer (Odocoileus hemionus) infected with foot-and-mouth disease. A considerable rise in temperature was observed in thermograms as early as 2 days before the occurrence of the first disease symptoms.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…Positive research outcomes prompted scientists to investigate the effectiveness of thermographic methods in diagnosing non-invasive diseases in wild animals. Dunbar et al (2009) used infrared thermography to detect temperature changes in mule deer (Odocoileus hemionus) infected with foot-and-mouth disease. A considerable rise in temperature was observed in thermograms as early as 2 days before the occurrence of the first disease symptoms.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…The results indicate IRT as a promising screening technology for a quick selection of potentially infected animals for confirmatory diagnostic testing during FMD outbreaks. Thermograms of the mouth and feet of mule deer (Odocoileus hemionus) experimentally infected with FMDV revealed that only IRT pictures of the feet provided information useful in disease screening; foot temperatures increased significantly as lesions developed (12). This increase started 48 hours before any disease lesions were observed, indicating that disease detection before lesion development may be possible.…”
Section: Infrared Thermography As a Diagnostic Tool For An Early Detementioning
confidence: 99%
“…23 Infrared imaging has been an effective disease surveillance tool in some situations, for example, as a screening tool for rabies in raccoons and FMD in ungulates. 10,11 Work is beginning on the use of temporary feed stations for feral swine. The stations may minimize migration, allow scientists to conduct remote disease surveillance through infrared imaging, and permit administering vaccines, therapeutics, or toxicants for disease management.…”
Section: Current and Potential Techniques For Disease Management In Wmentioning
confidence: 99%